Protein patterns of brush-border fragments in congenital lactose malabsorption and in specific hypolactasia of the adult - Freiburghaus, A U; Schmitz, J; Schindler, M; Rotthauwe, H W; Kuitunen, P; Launiala, K; Hadorn, B (The New England journal of medicine, 1976)
Brush-border membrane proteins of the small-bowel mucosa were separated on polyacrylamide gels from intestinal biopsy specimens obtained from four children with congenital lactose malabsorption and from two adults with specific hypolactasia. In three patients with the congenital type of lactase deficiency the protein band corresponding to brush-border lactase was reduced in intensity, but was never completely absent. No difference in gel patterns was detected when this pattern in congenital deficiency was compared to that obtained from the two patients with adult-type selective hypolactasia. In one patient with congenital lactose malabsorption the protein band corresponding to lactase activity was not detectable. The findings suggest that the mechanisms leading to low lactase activity in the congenital and adult forms of lactose intolerance are similar.